DETERMINAN DIGITALISASI PAJAK MELALUI NIAT PERILAKU - Jufri, Nurhayati; Yuliza, Arma; Yulian Mela, Fefti; Nofrianty, Nofrianty (Jurnal Analisa Akuntansi dan Perpajakan, 2024)
This research aims to analyze the influence of the Self Assessment System, Click, Call and Center, Hedonic Motivation and Facilitating Conditions on Tax Digitalization with Taxpayer Behavioral Intentions as an Intervening Variable, on Individual Taxpayers registered at KP2KP Pasir Pengaraian, Rokan Hulu Regency. The data source is primary data obtained from distributing questionnaires. The data analysis method uses the Structural Equation Modeling (SEM) model with the Partial Least Square (PLS) approach. The research results show that Click, Call and Center have an effect on Tax Digitalization while Self Assessment System, Hedonic Motivation and Facilitating Conditions have no effect on Tax Digitalization. Keywords: Self Assesment System, Click, Call and Center, Hedonic Motivation, Facilitating Condition, Tax Digitalitation and Behavior Intention